THE INFLUENCE OF THE LEADERSHIP STYLE OF THE HEAD OF PENALTY INSTITUTIONS AND THE MANAGEMENT OF ISLAMIC RELIGIOUS DEVELOPMENT ON THE MENTAL SPIRITUAL OF PRISONERS IN CLASS II-A PENALTY INSTITUTION, KUNINGAN, WEST JAVA - Asep Rohani (Publikasi Indonesia, 2023)
Leaders have a major role in the direction and change of an organization. Visionary leaders can give color to organizational change and direction, while leaders who can guide, formulate and control policies within the organization are obligations that are given spontaneously in their status as leaders both structurally and culturally. Education is the foundation and the main capital in building a nation so that a leader who plays a role in education both conceptually and technically is needed. In the Islamic concept of a leader, every individual is a leader, and the smallest leadership in the order of the leadership concept is to lead oneself. This study used a survey method with correlation techniques to determine the influence of leadership style and management of Islamic religious development on the spiritual mentality of inmates at Class II A Penitentiary, Kuningan, West Java. The results of the study show that the leadership style and management of Islamic religious development have an effect on the spiritual mentality of prisoners in the institution. However, the influence of leadership style on the development of Islam in the institution is considered low.